Analisis Kinerja Protokol Routing Ad Hoc On Demand Distance Vector (AODV) Pada Jaringan Vehicular Ad Hoc Network (VANET) Berdasarkan Variasi Model Jalan - Dedy Andrean Ardiansyah; Rakhmadhany Primananda; Adhitya Bhawiyuga (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
VANET (Vehicular Ad Hoc Network) is a wireless network technology developed from MANET (Mobile Ad Hoc Network) which is devoted for motorized vehicles. The main application of VANET technology is to realize better and safer traffic management. However, due to the high mobility of vehicles and varying road conditions, the most serious problem in VANET is the efficiency of the search process and maintaining network routes. AODV (Ad Hoc on Demand Distance Vector) is one solution to the VANET problem which is one of the reactive routing protocols. Variations of road models in Indonesia are divided into four groups based on the prevailing speed namely the freeway, inter-city roads, urban roads and residential roads. In each of these environments a simulation test was carried out with a difference in the number of vehicles. The simulation is carried out using Network Simulator v2.35 (NS-2.35) and SUMO as mobility generator. AODV performance is measured based on the parameters of average throughput, packet delivery ratio, and end-to-end delay in sequence. Test result on the freeway resulted in 111.48 KBps, 40.99 %, 0.14676 seconds. Test result on inter-city roads 156.20 KBps, 58.08 %, 0.08036 seconds. Test result on urban roads 210.07 KBps, 77.18 %, 0.05839 seconds. Whereas test result on residential roads 212.82 KBps, 77.27 %, 0.03362 seconds. These results show that the road model in Indonesia with the performance of the AODV routing protocol on the VANET network from the best to the worst in sequence is a residential road model, an urban road model, an inter-city road model, and freeway model.